Pengembangan Aplikasi Virtual Reality Untuk Pembelajaran Tentang Manasik Haji - Astuti, Ika Asti; Umri, Buyut Khoirul; Akbar, Muhammad Alfian Syaifullah (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
This study aims to develop a Virtual Reality-based learning medium for Manasik Haji to help users understand the procedures of Hajj in an interactive and realistic way. The application was designed through three main phases: planning, development, and testing. The application's key features include several stages of Manasik Haji, such as Ihram, Wukuf, Tawaf Ifadah, Sa'i, Stoning of the Jamarat, Tahallul, Mabit, and Tawaf Wada. The application testing was conducted using the black box method to ensure that all features function as intended, and the System Usability Scale (SUS) was utilized to measure the application's usability level. The SUS score obtained after the testing was 76, which falls into Grade B, indicating that the application has a good usability level. However, there are still areas for improvement, such as enhancing interactive features, improving overall usability aspects, and conducting tests with a more diverse group of users.